ANALISIS KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN PENDEKATAN STEM - Janatan Salsabiela, Hana; Dwiyanti, Ririn; Setiyawati, Valentina; Wahyudi, Apri (Universitas Negeri Medan, 2024)
Abstract: This study analyzes the readiness of elementary teachers to implement the STEM approach at SD Negeri 1 Putra Buyut. A qualitative descriptive method with snowball sampling was used to select informants, including the principal and teachers. Data were collected through interviews and classroom observations. Results showed that only 3 out of 8 teachers understood the STEM concept well. Most struggled with integrating disciplines and applying project-based learning. The study recommends continuous training to improve teachers' understanding and STEM implementation in elementary education. Keyword: STEM approach; teacher readiness; elementary education. Abstrak: Penelitian ini menganalisis kesiapan guru SD dalam menerapkan pendekatan STEM di SD Negeri 1 Putra Buyut. Metode deskriptif kualitatif dengan snowball sampling digunakan untuk memilih informan, melibatkan kepala sekolah dan guru. Data dikumpulkan melalui wawancara dan observasi kelas. Hasil penelitian menunjukkan bahwa hanya 3 dari 8 guru memahami konsep STEM dengan baik. Sebagian besar kesulitan dalam mengintegrasikan disiplin ilmu dan metode pembelajaran berbasis proyek. Studi ini merekomendasikan pelatihan berkelanjutan untuk meningkatkan pemahaman dan implementasi STEM di pendidikan dasar. Kata Kunci: STEM; kesiapan guru; pendidikan dasar.